MEDICAL DEVICE INNOVATION IN SOUTH AFRICA: EVOLUTION OF COLLABORATION NETWORKS (2001-2013) - de Jager, Kylie; Chimhundu, Chipo; Saidi, Trust; Douglas, Tania S. (The South African Journal of Industrial Engineering, 2019)
The evolution of medical device development in South Africa was investigated for the period 2001-2013. Collaboration networks for four sectors — academia, healthcare, industry, and science and support — were derived from a bibliometric study. Centrality measures identified dominant institutions. New actors entering the networks either exhibited preferential attachment to these institutions, or joined the network as part of an isolated cluster. Of the new institutions, foreign collaborators seldom stayed beyond five years, while local institutions seldom left after entering the field. Over the 13-year period, local collaboration activity persisted, while local-foreign collaborations were seen to decline. Over time, the network topology became more akin to that of a small-world network. The findings of the study may support innovation management by guiding institutional strategies for effective collaboration.